2016
DOI: 10.1111/1756-185x.12912
|View full text |Cite
|
Sign up to set email alerts
|

Primary Sjögren's syndrome is associated with significant cognitive dysfunction

Abstract: Results of this study suggest that cognitive dysfunction is quite prevalent in PSS patients without being associated with studied antibodies.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
19
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(21 citation statements)
references
References 30 publications
1
19
0
1
Order By: Relevance
“…Our cohort included 64 patients, which is a comparatively large number for a rare disease. More importantly, the threshold definition of cognitive impairment was often lower in comparison to our applied definition, which results in a more robust testing on our part, antagonizing overestimation 10 . Finally, in‐between‐study‐comparability is diminished, as the applied methodology shows a wide variety.…”
Section: Discussionmentioning
confidence: 83%
See 1 more Smart Citation
“…Our cohort included 64 patients, which is a comparatively large number for a rare disease. More importantly, the threshold definition of cognitive impairment was often lower in comparison to our applied definition, which results in a more robust testing on our part, antagonizing overestimation 10 . Finally, in‐between‐study‐comparability is diminished, as the applied methodology shows a wide variety.…”
Section: Discussionmentioning
confidence: 83%
“…Extraglandular neurological manifestations of Sjögren’s syndrome are increasingly recognized, forming the entity of Neuro‐Sjögren 3–7 . While peripheral neuropathy and cranial nerve affection 4,5 are the most prevalent neurological symptoms of Sjögren’s syndrome with rates of up to 60%, there have been several studies suggesting the involvement of the central nervous system through spinal cord involvement, headache, 8 and cognitive dysfunction 9–12 . Neuropsychological testing in patients with Sjögren’s syndrome has hitherto been performed on mostly rheumatological cohorts with the typical female preponderance 13 .…”
Section: Introductionmentioning
confidence: 99%
“…This cohort had a short disease duration (3.5 years) which may suggest that cognitive dysfunction appears early after disease diagnosis. Similarly, Tezcan et al 18 identified cognitive dysfunction by several standardized cognitive tests in pSS patients reporting a prevalence of 78.8%. This group had low disease activity (SS Disease Activity Index score 2.06 ± 0.11) and duration (12 months).…”
Section: Discussionmentioning
confidence: 86%
“…Both mechanisms would make the correlation stronger but for different reasons. Although the specific cellular/biochemical mechanisms for such changes in correlation are unknown, they are likely to share similar mechanisms that underlie brain dysfunction in other autoimmune or inflammatory brain disorders (Selmi et al, 2016), including neuropsychiatric lupus (Belmont et al, 1996, Menon et al, 1999, Omdal et al, 2005), rheumatoid arthritis (Shin et al, 2012), Sjögren's syndrome (Tezcan et al, 2016), and psoriasis (Gisondi et al, 2014). A special case is autoimmune encephalitis where the investigation of cellular autoimmune mechanisms has progressed appreciably (Armangue et al, 2015, Boronat et al, 2013, Clemente-Casares et al, 2016, Dalmau and Rosenfeld, 2008, Dalmau and Rosenfeld, 2014, Linnoila et al, 2014).…”
Section: Discussionmentioning
confidence: 99%